A Model of Bulk Supersymmetry in Warped Spacetime - Hieu, Tran Minh (Communications in Physics, 2016)
The Randall-Sundrum solution to the hierarchy problem in the brane-world scenario has made a significant impact on the development of model building.We investigate in this paper a model of supersymmetry in a 5D spacetime with the Randal-Sundrum warped metric.The minimal supersymmetric extension of the standard model (MSSM) superfields propagate in the bulk between the UV and IR branes at separated orbifold fixed points, while the hidden sector in charge of supersymmetry breaking is confined on the UV brane.We derive the 4D effective action from the original 5D action of the underlying theory.The effective 4D Yukawa couplings and all the soft supersymmetry breaking terms are calculated in terms of the 5D theory's coefficients. We comment on the important role of the bulk mass parameter in the relation with the geometrical properties of particles.